1991
DOI: 10.1073/pnas.88.14.6107
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine effects on nerve blood flow, vascular permeability, electrophysiology, and oxygen free radicals.

Abstract: Since advanced glycosylation end products have been suggested to mediate hyperglycemia-induced microvascular atherogenesis and because aminoguanidine (AG) prevents their generation, we examined whether AG could prevent or ameliorate the physiologic and biochemical indices of streptozotocin (STZ)-induced experimental diabetic neuropathy. Four groups of adult Sprague-Dawley rats were studied: group I received STZ plus AG (25 mg kg'1 day-1), group II received STZ plus AG (50 mg-kg'1day-1), group HI received STZ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
110
5
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(133 citation statements)
references
References 21 publications
16
110
5
2
Order By: Relevance
“…As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
Section: Discussionsupporting
confidence: 56%
“…We have previously shown that endothelialdependent vascular relaxation of arterioles that provide circulation to the region of the sciatic nerve is impaired by diabetes [35,36]. In the present study we sought to determine the effect treatment of diabetic rats with sorbinil, an aldose reductase inhibitor, aminoguanidine, an inhibitor of nonenzymatic glycation, or myoinositol supplementation has on EBF, MNCV as well as vascular relaxation of arterioles that provide circulation to the region of the sciatic nerve.As has been previously reported, we demonstrate that treating streptozotocin-induced diabetic rats with sorbinil or aminoguanidine significantly improves the reduction in EBF and slowing of MNCV [3][4][5][6][7][8][9][10][11][12][24][25][26][27][28]. In sorbinil treated diabetic rats EBF and MNCV remained suppressed by 15 and 18%, respectively compared to controls, whereas in aminoguanidine treated rats EBF and MNCV, compared to controls, was decreased by 6 and 16%, respectively.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…There are several published reports on the ability of aminoguanidine to inhibit AGE formation in vivo. [68][69][70][71][72][73][74][75][76][77] A recent report showed the ability of aminoguanidine to prevent the development of diabetic retinopathy in diabetic dogs followed for 5 years. 78 Optimism for the clinical use of aminoguanidine has been tempered by the gradual realisation that aminoguanidine also inhibits a range of other important pathways, most notably generation of nitric oxide by eNOS, which may increase nonspecific and unwanted side effects of the drug.…”
Section: Protein Glycationmentioning
confidence: 99%